2012
DOI: 10.1039/c2py20457f
|View full text |Cite
|
Sign up to set email alerts
|

PolyPEGylated nanodiamond for intracellular delivery of a chemotherapeutic drug

Abstract: Water dispersible and biocompatible polyPEGylated ND nanoparticles were prepared via surface-initiated atom transfer radical polymerization. Cell internalization study reveals that ND nanoparticles facilitate the transport of doxorubicin hydrochloride into A549 cells, indicating their potential applications in cancer therapy.Over the past few decades, carbon nanomaterials (CNMs) have attracted a great deal of scientific and technological attention due to their unique structure and remarkable electronic, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…[36][37][38][39] Therefore, PEG has been introduced to the ND, which can not only improve the dispersion, but also reduce the interaction with cells to reducing non-specific effects, and prolong the blood circulation time. [40][41] We have prepared ND-PEG via an ester band and found that PEGylated ND showed enhanced dispersity and stability in vitro under the physiological environment or in cell culture medium in our previous study. 42 Unfortunately, the Taking into account the necessity of high drug loading, augmented treatment efficiency and targeting ability for tumor, a novel nanodrug based on free DOX physical adsorption onto PEGylated ND in sodium citrate medium was designed (Scheme 1).…”
Section: Introductionmentioning
confidence: 96%
“…[36][37][38][39] Therefore, PEG has been introduced to the ND, which can not only improve the dispersion, but also reduce the interaction with cells to reducing non-specific effects, and prolong the blood circulation time. [40][41] We have prepared ND-PEG via an ester band and found that PEGylated ND showed enhanced dispersity and stability in vitro under the physiological environment or in cell culture medium in our previous study. 42 Unfortunately, the Taking into account the necessity of high drug loading, augmented treatment efficiency and targeting ability for tumor, a novel nanodrug based on free DOX physical adsorption onto PEGylated ND in sodium citrate medium was designed (Scheme 1).…”
Section: Introductionmentioning
confidence: 96%
“…As compared with the pristine CNTs, the funcitonalized CNTs have demonstrated to be better performance in heavy metal ion removal [17,18]. Previously, a number of surface modification strategies such as surface oxidation with concentrated acid, non-covalent with surfactants and amphiphilic polymers, in situ polymerization and hybridized with inorganic nanomaterials have been reported [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. On the other hand, different physical methods such as plasma irradiation and gamma-irradiation have also developed for surface modification of CNTs.…”
Section: Introductionmentioning
confidence: 97%
“…For example, we have previously demonstrated that PEGylation of nanodiamonds could be achieved through both graft to method and graft from method [54]. These PEGylated nanodiamonds showed high water dispersibiliy and can be used for intracellular delivery of anticancer drug (DOX) into cells with good performance [60]. More importantly, PEGylation is also an important strategy for avoiding nanomaterials swallowed by reticuloendothelial system in vivo, which is very useful for improving the therapeutic index and decreasing the adverse effects of drugs [59].…”
Section: Resultsmentioning
confidence: 97%
“…The cell viability was further used to quantitatively evaluate the biocompatibility of CNT-PDA-PEGMA using the WST assay as described in our previous reports [51][52][53]. Briefly, cells were seeded in 96-well microplates at a density of 5 × 10 4 cells per mL in 160 L Then the cells were washed with PBS for three times to remove the uninternalized nanoparticles.…”
Section: Biocompatibility Evaluation Of Cnt-pda-pegmamentioning
confidence: 99%